ANALISIS RESEPSI KHALAYAK MENGENAI STIGMATISASI PENYINTAS GAGAP MELALUI TAYANGAN YOUTUBE MENJADI MANUSIA (Studi pada Komunitas Indonesian Stuttering Community) - Muhamad Carvin Syah, (2022)
This study aims to find the meaning formed by the audience about the stigma of people with stuttering disorders through YouTube shows on the Menjadi Manusia channel, on the program "Berbagi Perspektif" Episode 117 - From Dwiki Perspective About Speech Disorders and Being the Object of Jokes. The video was chosen by the author as the object of research because it is considered quite relevant to the phenomenon that occurs in society regarding stuttering speech disorders and the stigma attached to its survivors. In this study, the authors chose the Indonesian Stuttering Community (ISC) as the research subject because it is a community that accommodates stuttering speech disorder survivors in Indonesia. The author uses the encoding-decoding theory initiated by Stuart Hall. This research uses reception analysis method with a qualitative approach. The author examines using several research concepts, namely; communication, mass communication, reception, audience, stigmatization, survivors, stuttering, social media, and YouTube. The data collection technique was done by purposive sampling technique. The results showed that from the informants, there were 4 (four) informants belonging to the Dominant Hegemonic position and 2 (two) informants belonging to the Negotiation position. The differences in meaning conveyed by information are based on the different backgrounds possessed by each other informant about life experience, religion believed to be between, socio-geographic (residential environment), level of knowledge or education and how to use social media.